Arabidopsis thaliana mutants disrupted in lipid mobilization. (December 2000) - Lange, P. R.; Graham, I.
Abstract : To isolate mutants in the process of lipid mobilization during post-germinative growth we employed a screen using the pro-herbicide 2, 4-dichlorophenoxybutyric acid (2, 4-DB). The phenotypes of a number of 2, 4-DB-resistant mutants are compared with previously characterized mutants disrupted in β-oxidation or the glyoxylate cycle. We conclude that the strength of 2, 4-DB resistance and the ability of the seedlings to grow in the absence of exogenous sugar are inversely correlated. Sugar dependence of 2, 4-DB-resistant seedlings is a consequence of impaired storage-lipid mobilization.